Mechanosensitivity in the enteric nervous system - Mazzuoli-Weber, Gemma; Schemann, Michael (Frontiers in Cellular Neuroscience, 2015)
The enteric nervous system (ENS) autonomously controls gut muscle activity. Mechanosensitive enteric neurons (MEN) initiate reflex activity by responding to mechanical deformation of the gastrointestinal wall. MEN throughout the gut primarily respond to compression or stretch rather than to shear force. Some MEN are multimodal as they respond to compression and stretch. Depending on the region up to 60% of the entire ENS population responds to mechanical stress. MEN fire action potentials after mechanical stimulation of processes or soma although they are more sensitive to process deformation. There are at least two populations of MEN based on their sensitivity to different modalities of mechanical stress and on their firing pattern. 1) Rapidly, slowly and ultra-slowly adapting neurons which encode compressive forces. 2) Ultra-slowly adapting stretch-sensitive neurons encoding tensile forces. Rapid adaptation of firing is typically observed after compressive force while slow adaptation or ongoing spike discharge occurs often during tensile stress (stretch). All MEN have some common properties: they receive synaptic input, are low fidelity mechanoreceptors and are multifunctional in that some serve interneuronal others even motor functions. Consequently, MEN possess processes with mechanosensitive as well as efferent functions. This raises the intriguing hypothesis that MEN sense and control muscle activity at the same time as servo-feedback loop. The mechanosensitive channel(s) or receptor(s) expressed by the different MEN populations are unknown. Future concepts have to incorporate compressive and tensile-sensitive MEN into neural circuits that controls muscle activity. They may interact to control various forms of a particular motor pattern or regulate different motor patterns independently from each other.